A taxonomic revision of the ground spiders of the genus Apopyllus (Araneae: Gnaphosidae) - Azevedo, Guilherme H.f.; Ott, Ricardo; Griswold, Charles E.; Santos, Adalberto J. (Zootaxa, 2016)
The American gnaphosid genus Apopyllus Platnick & Shadab is found from southern Mexico to southern Argentina. It can be diagnosed by the complex shape of the RTA, by the membranous tegular extension, the long coiled embolus, the retrolateral incision on the cymbium, the long convoluted copulatory duct extending anteriorly to the copulatory openings and by the presence of paramedian epigynal pockets and of an anterior ridge on the epigynum. The RTA characters are important in species taxonomy but the complex shape and variation of the RTA hampers identification, especially regarding the two most common species: A. suavis (Simon) and A. silvestrii (Simon). In this paper the genus is revised, the genital morphology is described, and homology between its components and those of other genera is discussed. Apopyllus suavis is considered a senior synonym of Apopyllus pauper (Mello-Leitão) and A. iheringi (Mello-Leitão). Four new species are described from Brazil: A. aeolicus, A. atlanticus, A. centralis and A. gandarela.